DEVELOPMENT OF MUSICAL ABILITIES OF PRESCHOOL EDUCATIONAL ORGANIZATIONS - U. Hamrayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes the content and methods of working with preschoolers, students with muscular disabilities. Psychological and physiological conditions are also described.